Fostering Critical and Creative Thinking in Mathematics: A Study on Brain-Based and Problem-Based Learning - Rivaldo Paul Telussa; Jovial Kaihatu; Paul Arjanto (Institut Agama Islam Negeri Palopo, 2024)
The study looked at how using brain-based learning (BBL) and problem-based learning (PBL) together could help 7th-grade students improve their critical and creative thinking in math at SD Negeri 02 Nabire. They wanted to see if these methods could fill gaps in traditional teaching by making learning more inclusive. They used a type of research design that compares two groups, one getting the new teaching methods and the other not, to see if there's a difference. They tested 58 students before and after the new methods using various statistical tools and found that both BBL and PBL made a big difference in how well students could think critically and creatively. This study adds to what we know about how BBL and PBL can make math learning better. It shows that when teaching matches how students learn best, they do better in math and are more ready for future challenges.